Case Report: Child with Amelogenesis Imperfecta - Ghelichli, Maryam; Sohrabi , Sina (Shahroud Journal of Medical Sciences, 2025)
Amelogenesis imperfecta (AI) is a rare genetic disorder that affects children and adults. These patients have very untidy and discolored teeth and experience many physical and psychological problems. The present patient is a 10-year-old girl who was diagnosed with amelogenesis imperfecta with great difficulty and existing limitations, underwent temporary composite treatment in a short period, and returned to the arms of her family and society with a beautiful appearance and great self-confidence.